Evolution characteristics of overburden structure and stress in strong mining of the deep coal seam: a case study - Zou, Junpeng; Wang, Man; Bai, Lu; Yan, Chongwei (Frontiers in Earth Science, 2023)
As coal resources are gradually being extracted at depth, the overlying strata movement behavior and stress environment become complex and violent, leading to the frequent triggering of strong dynamic hazards. To promote the productivity and effectiveness of mining activities, this paper investigated the evolution characteristics of overburden structure and stress in deep mining by using theoretical analysis, on-site monitoring, and numerical simulation. Based on key strata theory, key layers were determined, and how their movement states have a controlling effect on surface subsidence was analyzed. The evolution process of the overburden spatial structure in deep mining was revealed, which was consistent with the “O-X” type structure. The surrounding rock stress at the working face has gone through three stages, violent change, slow increase, and fluctuant increase, and strong strata behaviors appear because of the fracture and collapse of key layers. The goaf will have a significant effect on the structure, stress, and deformation of the overlying rock, which results in a larger deformation of the surrounding rock within the vicinity. The narrow coal pillar fails to maintain the stability of the overburden structure when the stress exceeds the bearing capacity. The deformation law of the surrounding rock at the roadway was studied, concluding that the existence of the goaf leads to a further increase in deformation.